Efficiency of the food supplement "Tribulus" used by athletes - Milasius, K.; Dadeliene, R. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Tribulus is one of the quite popular food supplements used by a big number of athletes. When investigation of the effect of Tribulus Terrestris had been started more widely, it was found out that this herb had influence on masculine hormone testosterone level in blood, on strengthening immunity, improving endurance, when its effect was started to be analyzed widely (Antonio et al., 2000; Elder et al., 2001; Rogerson et al., 2004). The aim of the research was establishing the influence of food supplement Tribulus on athletes` physical development, physical working ability, aerobic functional capacity, blood circulation and respiratory systems. Methods: The sample of the research included thirty-two 20-22 year old athletes. The first experimental group consisted of 20 individuals. For 20 days they used 3 capsules of the food supplement Tribulus (produced by the USA Company (OPTIMUM NUTRITION) a day. The control group (n=12) participants did not consume any food supplements. Results: Their relative AAMP the members of experimental group, having used food supplement Tribulus for 20 days, have increased from 16,3±1,1 to 17,2±1,5 W/kg (F= 5,12, p=0,03). Relative alactate glycolyte working capacity (AGWC), when work duration is 30-s, in 20 days have increased from 8,2±0,8 to 8,7±0,8 W/kg (F=4,34, p=0,04). VO2max at the critical intensity threshold have increased from 50,3 to 55,4 ml/min/kg (F=3,63, p=0,07). During the experimental period still growing erythrocyte sedimentation rate, statistically importantly increased percentage of granulocytes and decreased percentage of leucocytes show negative impact of this food supplement on changes of leucocytes formula in athletes` blood. Accordingly, complete blood counts (CBC) for athletes who consume food supplement Tribulus 25 mg per 1 kg of body mass for the period of 10 days or longer must be carried out. Creatinkinase concentration in athletes` blood statistically importantly has increased and creatinine amount has had a tendency to decline during 20 days period of consuming food supplement Tribulus. The declining tendency of urea, cholesterol and bilirubin concentrations has appeared. The concentration of blood testosterone increased statistically reliable during the first half (10 days) of the experiment; it did not grow during the next 10 days while consuming Tribulus still.